Description Of Blood Pressure After Injection Of Spinal Anesthesia In Caesaria Sectio Patients At Dr. Soedirman Hospital Kebumen - Primadiyadi, Syaikh Azib Esa; Susanto, Amin; Lintang Suryani, Roro (Java Nursing Journal, 2024)
Background: Every surgical procedure cannot be separated from anethesia. Brodly speaking, anesthesia divideed into three, general anethesia, regional anesthesia and local anethesia. Seectio caaesarea is one of the most frequently performed operations for birthing process. SC is type of fetal delivery through an open abdominal incision (laparatomy) and an incision in the uterus (hysterectomy). Spinal anethesia is atechnique that has anagesic properties that relieves the patient’s pain but still maintains the patient’s consciousness. Purpose: the aim of this study was to determinne the picture of blood pressure after spinal anethesia injection in pre-caesarean section patients at Dr soedirman Hospital Kebumen.  Methods: The method used in this research is quantitaive observational analysis. Quantative research with analytical observational research, namely observing a phenomenon between risk factors and effect factors.Results: The results of this study show that caracteristics of the most respondents in this study were 26-35 years old, 25 respondents (48,1%), and 35 respondents (67,3%) with a history of caesarean section for the first time. Conclusions: in generaal, resnpondents did not experience changes in blood pressure after spinal anethesia infection, but some patients experienced hypotension.